DON'T QUIT YOUR DAY JOB the 6 mindshifts you need to rise and thrive at work. - Knox, Aliza (JOHN WILEY & SONS AUSTRAL, 2021)
Learn how to survive and thrive within organisations In Don't Quit Your Day Job, former Google and Twitter executive Aliza Knox delivers hands-on, practical steps for achieving career success. Driven by Knox's four decades working in and leading some of the world's most celebrated firms, and featuring candid accounts of other people's successes and missteps in global tech, consumer goods, healthcare, academia, social services and more, this book is an essential guide to integrating your professional and personal goals to build a fulfilling, complete life. The book also includes: Invaluable advice to power up your people skills and soft skills, and how to care for your career like you would any other relationship. Effective perspectives to help balance your working life and personal life and to build stamina for the long haul. A global outlook that reveals how to excel in today's hybrid, often dispersed world of work. Whether you're just starting your first job or you're ready to rise to the C-suite, Don't Quit Your Day Job will help you advance and flourish in the workplace.